Molecular Mechanisms Associated With PTHrP‐Induced Proliferation of Colon Cancer Cells. Issue 12 (15th October 2014) - Martín, María Julia; Calvo, Natalia; de Boland, Ana Russo; Gentili, Claudia
ABSTRACT Parathyroid Hormone‐related Protein (PTHrP) is normally produced in many tissues and is recognized for its endocrine, paracrine, autocrine and intracrine modes of action. PTHrP is also implicated in different types of cancer and its expression correlates with the severity of colon carcinoma. Using the human colon cell line Caco‐2 we recently obtained evidence that PTHrP, through a paracrine pathway, exerts a protective effect under apoptotic conditions. However, if exogenous PTHrP is able or not to induce the proliferation of these intestinal tumor cells is not known. We found that PTHrP treatment increases the number of live Caco‐2 cells. The hormone induces the phosphorylation and nuclear translocation of ERK 1/2, α p38 MAPK, and Akt, without affecting JNK phosphorylation. In addition, PTHrP‐dependent ERK phosphorylation is reverted when PI3K activity was inhibited. Following MAPKs nuclear translocation, the transcription factors ATF‐1 and CREB were activated in a biphasic manner. In addition PTHrP induces the translocation into the nucleus of β‐catenin, protein that plays key role in maintaining the growth and proliferation of colorectal cancer, and increases the amount of both positive cell cycle regulators c‐Myc and Cyclin D. Studies with ERK1/2, α p38 MAPK, and PI3K specific inhibitors showed that PTHrP regulates Caco‐2 cell proliferation via these signaling pathways. In conclusion, the results obtained in this work expand our knowledge on the role of exogenous PTHrP in intestinal tumor cells and identify the signaling pathways that are involved in the mitogenic effect of the hormone on Caco‐2 cells. J. Cell. Biochem. 115: 2133–2145, 2014. © 2014 Wiley Periodicals, Inc.